The Involvement of Microtubules and Actin during the Infection of Japanese Encephalitis Virus in Neuroblastoma Cell Line, IMR32 - Magdline Sia, Henry Sum (Hidawi Publishing Coperation, 2014)
The role of the cytoskeleton, actin, and microtubules were examined during the process of Japanese encephalitis (JEV) infection in a human neuroblastoma cell line, IMR32. Cytochalasin D and nocodazole were used to depolymerise the cellular actin and microtubules, respectively, in order to study the effect of JEV infection in the cell. This study shows that depolymerisation of the actin cytoskeleton at early process of infection inhibits JEV infection in the cell; however infection was not inhibited when depolymerisation occurred at the later stage of infection.The microtubules, on the other hand, are required at 2 points in infection. The antigen production in the cells was inhibited when the infected cells were treated at time up to 2 hours after inoculation and there was no significant effect at later times, while the viable virus released continued to be affected until 10 hours after inoculation. In conclusion, infection of JEV in IMR32 cells required actin to facilitate early process in infection and the microtubular network is utilised as the transport system to the virus replication site and the release of mature virus.